Battery cell, battery device and power-consuming device

By using small-particle graphite and doped elements in the negative electrode sheet of lithium-ion battery, and combining linear conductive agents, the problem of insufficient lithium-ion conduction and embedding capabilities of lithium-ion batteries under fast charging conditions is solved, and the fast charging performance and pole-sheet structure stability of the battery are significantly improved.

CN119786702APending Publication Date: 2025-04-08CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411997274.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Under the fast charging conditions of existing lithium-ion batteries, the lithium-ion conduction and embedding capabilities of the negative electrode plate are insufficient, resulting in poor fast charging performance and easy to cause unstable electrode plate structure during charging.

Method used

Graphite with a smaller particle size (2-20 μm) and doped elements is used as the negative electrode active material, and combined with linear conductive agents, the transmission channels of lithium ions and electrons are improved and the structural stability of the electrode sheet is enhanced.

Benefits of technology

It improves the lithium ion conduction and embedding capability of the battery under fast charging conditions, enhances the structural stability of the negative electrode sheet, and thus improves the fast charging performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786702A_ABST
    Figure CN119786702A_ABST
Patent Text Reader

Abstract

The present application relates to a battery cell, a battery device and an electric device, wherein the negative electrode active material of the battery cell comprises graphite, the particle size Dv50 of the graphite is 2 to 20 μm, and the graphite comprises a doping element, the atomic radius of the doping element is greater than the atomic radius of the carbon element; the conductive agent in the negative electrode material layer comprises a linear conductive agent, and the aspect ratio of the linear conductive agent is 50 to 10000. The battery cell provided by the present application has good fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery cell, a battery device and an electrical device. Background Art

[0002] In recent years, secondary batteries represented by lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the popularization of secondary battery applications, higher requirements have been placed on their fast charging performance. Summary of the invention

[0003] The purpose of the present application is to provide a battery cell, a battery device and an electrical device. The battery cell mainly improves the lithium ion conduction and embedding ability of the negative electrode plate under fast charging conditions and the structural stability of the electrode plate, thereby improving the fast charging performance of the battery.

[0004] To this end, a first aspect of the present application provides a battery cell, including a positive electrode sheet, a separator and a negative electrode sheet;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; the negative electrode material layer comprises a negative electrode active material and a conductive agent;

[0006] The negative electrode active material includes graphite, the particle size Dv50 of the graphite is 2 to 20 μm, the graphite includes a doping element, and the atomic radius of the doping element is greater than the atomic radius of the carbon element;

[0007] The conductive agent includes a linear conductive agent, and the aspect ratio of the linear conductive agent is 50 to 10,000.

[0008] By using graphite materials with the above-mentioned smaller particle size (2-20 μm), the distance for active ions to enter the internal lattice from the surface of graphite particles is relatively short, and the solid phase transmission distance is short, which reduces the resistance of active ions to embed into graphite. In addition, doping elements with atomic radius larger than carbon are added to graphite. The doping modification of these elements makes the lattice spacing of graphite larger, which is conducive to the embedding of lithium ions. Therefore, it is beneficial to improve the dynamics of active ion embedding into graphite.

[0009] However, when the particle size of the graphite material is small, the bonding interface between the graphites becomes larger, and the force exerted on the lithium ions when transmitting between different graphites increases, which is not conducive to the transmission of lithium ions and electrons. Therefore, a linear conductive agent is used to increase the lithium ion transmission channel between the graphites to improve the transmission of lithium ions and electrons. When the above aspect ratio is adopted, the linear conductive agent can not only improve the transmission of lithium ions and electrons, but also the linear conductive agents are entangled with each other to form a mesh structure with certain gaps, which has a certain binding effect on the graphite material, can reduce the volume expansion of the graphite material during the lithium insertion process, and improve the structural stability of the negative electrode during the fast charging process.

[0010] In some embodiments, the doping element includes one or more of nitrogen, phosphorus, and sulfur.

[0011] The atomic radius of the above doping elements is larger than that of carbon, and they have good compatibility with the battery system and have no adverse effect on the battery performance. In addition, when the above elements are used for doping modification, they also have the advantage of being easy to prepare.

[0012] In some embodiments, the particle size Dv50 of the graphite and the aspect ratio of the linear conductive agent meet one of the following conditions:

[0013] The particle size Dv50 of the graphite is greater than or equal to 2 μm and less than or equal to 5 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 5000 and less than or equal to 10000; or

[0014] The particle size Dv50 of the graphite is greater than 5 μm and less than or equal to 10 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 2000 and less than 5000; or,

[0015] The particle size Dv50 of the graphite is greater than 10 μm and less than or equal to 20 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 50 and less than 2000.

[0016] Graphite materials are prone to expansion during the process of embedding lithium ions. During fast charging, the expansion phenomenon is more significant, which can easily lead to instability in the structure of the negative electrode plate. In order to better achieve the binding effect on graphite materials, linear conductive agents with different aspect ratios are used for graphite materials of different particle sizes to achieve a good coating effect, so as to better reduce the graphite expansion problem during fast charging. In general, when the graphite particle size is small, the use of linear conductive agents with a larger aspect ratio is conducive to forming a denser network and coating multiple graphite particles at the same time; when the graphite particle size is large, the use of linear conductive agents with a smaller aspect ratio is more conducive to the uniform dispersion of graphite particles and linear conductive agents, and plays a good coating role.

[0017] In some embodiments, in the negative electrode material layer, the mass ratio of the linear conductive agent is 0.02% to 1%.

[0018] When the mass proportion of the linear conductive agent is greater than or equal to 0.02%, it has a good improvement effect in improving ionic conductivity, improving electronic conductivity and inhibiting the expansion of graphite materials; when the mass proportion of the linear conductive agent is less than or equal to 1%, the negative electrode active material can correspondingly have a higher mass proportion, which is conducive to maintaining a good energy density.

[0019] In some embodiments, the diameter of the linear conductive agent is 5 to 20 nm; and / or,

[0020] The length of the linear conductive agent is 1 to 200 μm.

[0021] When the linear conductive agent has the above length, it can have good dispersibility and long-range ion conductivity and electrical conductivity. When the linear conductive agent has the above diameter, it has good mechanical properties, which is conducive to improving the restraint effect on the expansion of the graphite material.

[0022] In some embodiments, the linear conductive agent includes at least one of the following: single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanofibers.

[0023] The above-mentioned types of linear conductive agents have good ion conductivity and electrical conductivity, and have a certain bending stiffness. After forming a conductive network, they can play a certain restraining role on the expansion of graphite materials, increase the cohesion of the negative electrode plate, and help improve the stability of the battery under fast charging conditions.

[0024] In some embodiments, in the graphite, the atomic ratio of the doping element to the carbon element is 0.5% to 2%.

[0025] Doping elements are beneficial to increase the lattice spacing to reduce the resistance of lithium ion embedding. When the doping atomic ratio is greater than or equal to 0.5%, it can play a significant improvement role. The conductivity of carbon is better than that of doping elements such as nitrogen, phosphorus, and sulfur. Therefore, making the doping atomic ratio less than or equal to 2% is beneficial to make graphite have good conductivity.

[0026] In some embodiments, at least a portion of the surface of the graphite has an amorphous carbon coating layer; the thickness of the amorphous carbon coating layer is 2 to 20 nm.

[0027] Amorphous carbon has more pores and defects than graphite, allowing electrons to travel freely through it, thereby improving electronic conductivity and improving fast charging performance by increasing electron mobility efficiency.

[0028] In some embodiments, the graphite has a Raman spectrum of 1300-1400 cm-1 The peak intensity ID in the range of 1550-1650cm -1 The intensity ratio ID / IG of the peak intensity IG within the range is 0.5 to 1.5.

[0029] The ID value indicates the scattering peak intensity caused by defects or impurities in the graphite structure, reflecting the proportion of disordered structures in the material; the IG value mainly reflects the proportion of ordered and complete structures in the material. When the ID / IG ratio of the graphite material is within the above range, the graphite material has good crystallinity and moderate crystal defects, which helps to promote the rapid deintercalation of lithium ions while maintaining structural integrity, thereby improving the fast charging performance of the battery.

[0030] In some embodiments, the negative electrode material layer includes a first negative electrode film layer and a second negative electrode film layer, the first negative electrode film layer is closer to the negative electrode current collector than the second negative electrode film layer; the particle size Dv50 of the graphite in the first negative electrode film layer is smaller than the particle size Dv50 of the graphite in the second negative electrode film layer.

[0031] The first negative electrode film layer is farther away from the electrolyte than the second negative electrode film layer, and the resistance of lithium ions embedding into the graphite of the first negative electrode film layer is greater. Therefore, further reducing the particle size of the graphite in the first negative electrode film layer can shorten the lithium ion embedding path and reduce the resistance of lithium ion embedding. Using graphite with a relatively large particle size in the second negative electrode film layer can still meet the demand for lithium ion embedding under fast charging conditions, and also has good dispersibility and processing performance.

[0032] In some embodiments, the particle size Dv50 of the graphite in the first negative electrode film layer is 2 to 15 μm; and / or,

[0033] The particle size Dv50 of the graphite in the second negative electrode film layer is 5 to 20 μm.

[0034] When the graphite particle size in the first negative electrode film layer and / or the second negative electrode film layer is within the above range, it is beneficial to further improve the lithium ion embedding ability during the fast charging process.

[0035] A second aspect of the present application provides a battery device, which includes the battery cell described in the first aspect of the present application.

[0036] In a third aspect of the present application, an electrical device is provided, which includes the battery cell described in the first aspect of the present application, or the battery device described in the second aspect of the present application.

[0037] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used to illustrate the preferred embodiments and are not to be considered as limiting the present application. In the accompanying drawings:

[0039] Figure 1 is a schematic diagram of a battery cell according to an embodiment of the present application;

[0040] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;

[0041] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0042] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0043] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0044] Figure 6 is a schematic diagram of an electrical device using a battery cell as a power source according to an embodiment of the present application;

[0045] Description of reference numerals:

[0046] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 end cover. DETAILED DESCRIPTION

[0047] The exemplary embodiments of the present disclosure will be described in more detail below. It should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0048] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0049] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0051] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0052] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0053] In recent years, secondary batteries have made great progress. With the development of related technologies and the increase in demand, higher requirements have been put forward for the fast charging performance of secondary batteries. During the charging process, active ions (such as lithium ions) migrate to the negative electrode and embed into the negative electrode active material. Therefore, the negative electrode becomes one of the key components affecting the fast charging performance of secondary batteries.

[0054] In the embodiments of the present application, the lithium ion conduction and embedding ability of the negative electrode plate under fast charging conditions and the structural stability of the plate are improved mainly by applying modified graphite in the negative electrode and combining it with a linear conductive agent with a certain aspect ratio, thereby improving the fast charging performance of the battery.

[0055] The solutions described in the embodiments of the present application are applicable to battery cells, battery devices using the battery cells, and electrical devices using the battery cells or battery devices.

[0056] Battery Cell

[0057] In the embodiment of the present application, the battery cell may be a secondary battery. A secondary battery refers to a battery cell that can be continuously used by activating active materials by charging after the battery cell is discharged.

[0058] The battery cell may be a lithium ion battery, a sodium ion battery, a sodium lithium ion battery, a lithium metal battery, a sodium metal battery, a lithium sulfur battery, a magnesium ion battery, a nickel hydrogen battery, a nickel cadmium battery, a lead storage battery, etc. In some embodiments, the battery cell is a lithium ion battery.

[0059] [Electrode assembly]

[0060] A battery cell generally includes an electrode assembly. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, which is arranged between the negative electrode sheet and the positive electrode sheet. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through.

[0061] [Negative electrode]

[0062] In some embodiments, a battery cell is provided, which includes a positive electrode sheet, a separator, and a negative electrode sheet;

[0063] The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; the negative electrode material layer comprises a negative electrode active material and a conductive agent;

[0064] The negative electrode active material includes graphite, the particle size Dv50 of the graphite is 2 to 20 μm, the graphite includes a doping element, and the atomic radius of the doping element is greater than the atomic radius of the carbon element;

[0065] The conductive agent includes a linear conductive agent, and the aspect ratio of the linear conductive agent is 50 to 10,000.

[0066] Fast charging performance is affected by many factors, such as the speed at which active ions are embedded in graphite, the rate at which ions and electrons are transmitted in the negative electrode, etc.; in addition, high-rate charging can easily cause graphite expansion and subsequent powder and film loss, which is not conducive to fast charging.

[0067] On the one hand, by using graphite materials with the above-mentioned smaller particle size (2-20 μm), the distance for active ions to enter the internal lattice from the surface of graphite particles is relatively short, and the solid phase transmission distance is short, which reduces the resistance of active ions to embed into graphite. In addition, doping elements with atomic radius larger than carbon are added to graphite. The doping modification of these elements makes the lattice spacing of graphite larger, which is conducive to the embedding of lithium ions. Therefore, it is beneficial to improve the dynamics of active ion embedding into graphite.

[0068] On the other hand, when the particle size of the graphite material is small, the bonding interface between the graphites becomes larger, and the force exerted on the lithium ions when transmitting between different graphites increases, which is not conducive to the transmission of lithium ions and electrons. Therefore, a linear conductive agent is used to increase the lithium ion transmission channel between the graphites to improve the transmission of lithium ions and electrons. When the above aspect ratio is adopted, the linear conductive agent can not only improve the transmission of lithium ions and electrons, but also the linear conductive agents are entangled with each other to form a mesh structure with certain gaps, which has a certain binding effect on the graphite material, can reduce the volume expansion of the graphite material during the lithium insertion process, and improve the structural stability of the negative electrode during the fast charging process.

[0069] The particle size Dv50 is well known in the art and can be measured using instruments and methods well known in the art, for example, it can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0070] Graphite is doped with elements, and the doped elements can be measured using instruments and methods known in the art. For example, an organic element analyzer (EA) can be used to quantitatively analyze the elements.

[0071] Linear conductive agent refers to a conductive material with a linear structure. The aspect ratio of a linear conductive agent refers to the ratio of its length to its diameter, which can be detected by the following method: imaging the negative electrode plate through a scanning electron microscope or a transmission electron microscope, recording the length and diameter of the linear conductive agent and calculating the aspect ratio based on this.

[0072] In some embodiments, the particle size Dv50 of the graphite is 2 to 20 μm, for example, can be selected from about 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.

[0073] In some embodiments, the aspect ratio of the linear conductive agent is 50 to 10000, for example, can be selected from about 50, 100, 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, etc.

[0074] In some embodiments, the particle size Dv50 of the graphite is greater than or equal to 2μm and less than or equal to 5μm, for example, it can be about 2μm, 3μm, 4μm, 4.5μm, 4.9μm, 5μm, etc.; the aspect ratio of the linear conductive agent is greater than or equal to 5000 and less than or equal to 10000, for example, it can be about 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 9900, 10000, etc.

[0075] In some embodiments, the particle size Dv50 of the graphite is greater than 5 μm and less than or equal to 10 μm, for example, it can be about 5.1 μm, 6 μm, 7 μm, 8 μm, 9 μm, 9.5 μm, 9.9 μm, 10 μm, etc.; the aspect ratio of the linear conductive agent is greater than or equal to 2000 and less than 5000, for example, it can be about 2000, 2500, 3000, 3500, 4000, 4500, 4500, 4900, etc.

[0076] In some embodiments, the particle size Dv50 of the graphite is greater than 10μm and less than or equal to 20μm, for example, it can be about 10.1μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 19.5μm, 20μm, etc.; the aspect ratio of the linear conductive agent is greater than or equal to 50 and less than 2000, for example, it can be about 50, 100, 500, 1000, 1500, 1900, etc.

[0077] Graphite materials are prone to expansion during the process of embedding lithium ions. During fast charging, the expansion phenomenon is more significant, which can easily lead to instability in the structure of the negative electrode plate. In order to better achieve the binding effect on graphite materials, linear conductive agents with different aspect ratios are used for graphite materials of different particle sizes to achieve a good coating effect, so as to better reduce the graphite expansion problem during fast charging. In general, when the graphite particle size is small, the use of linear conductive agents with a larger aspect ratio is conducive to forming a denser network and coating multiple graphite particles at the same time; when the graphite particle size is large, the use of linear conductive agents with a smaller aspect ratio is more conducive to the uniform dispersion of graphite particles and linear conductive agents, and plays a good coating role.

[0078] In some embodiments, in the negative electrode material layer, the mass ratio of the linear conductive agent is 0.02% to 1%; for example, it can be about 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, etc.

[0079] When the mass proportion of the linear conductive agent is greater than or equal to 0.02%, it has a good improvement effect in improving ionic conductivity, improving electronic conductivity and inhibiting the expansion of graphite materials; when the mass proportion of the linear conductive agent is less than or equal to 1%, the negative electrode active material can correspondingly have a higher mass proportion, which is conducive to maintaining a good energy density.

[0080] In some embodiments, the diameter of the linear conductive agent is 5 to 20 nm, for example, about 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc. When the linear conductive agent has the above length, it can take into account good dispersibility and long-range ion conductivity and electrical conductivity.

[0081] In some embodiments, the length of the linear conductive agent is 1 to 200 μm, for example, about 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, etc. When the linear conductive agent has the above diameter, it has good mechanical properties and is conducive to improving the restraining effect on the expansion of the graphite material.

[0082] In some embodiments, the linear conductive agent includes at least one of the following: single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), and carbon nanofibers (CNFs).

[0083] The above-mentioned types of linear conductive agents have good ion conductivity and electrical conductivity, and have a certain bending stiffness. After forming a conductive network, they can play a certain restraining role on the expansion of graphite materials, increase the cohesion of the negative electrode plate, and help improve the stability of the battery under fast charging conditions.

[0084] In some embodiments, in the graphite, the atomic ratio of the element to the carbon element is 0.5% to 2%; for example, it can be about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.

[0085] Doping elements are beneficial to increase the lattice spacing to reduce the resistance of lithium ion embedding. When the doping atomic ratio is greater than or equal to 0.5%, it can play a significant improvement role. The conductivity of carbon is better than that of doping elements such as nitrogen, phosphorus, and sulfur. Therefore, making the doping atomic ratio less than or equal to 2% is beneficial to make graphite have good conductivity.

[0086] In some embodiments, at least a portion of the surface of the graphite has an amorphous carbon coating; the thickness of the amorphous carbon coating is 2 to 20 nm, for example, it can be about 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc.

[0087] Amorphous carbon has more pores and defects than graphite, allowing electrons to travel freely through it, thereby improving electronic conductivity and improving fast charging performance by increasing electron mobility efficiency.

[0088] Amorphous carbon refers to carbon materials with a very low degree of graphitization and crystallization, which are close to amorphous forms (or have no fixed shape and periodic structural regularity). The thickness of the amorphous carbon coating on the graphite surface can be detected by the following method: the negative electrode is imaged by transmission electron microscopy, and the thickness of the coating is measured and calculated based on the imaging results.

[0089] In some embodiments, the graphite has a Raman spectrum of 1300-1400 cm -1 The peak intensity ID in the range of 1550-1650cm -1The intensity ratio ID / IG of the peak intensity IG in the range is 0.5 to 1.5, for example, it can be about 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, etc.

[0090] The ID value indicates the scattering peak intensity caused by defects or impurities in the graphite structure, reflecting the proportion of disordered structures in the material; the IG value mainly reflects the proportion of ordered and complete structures in the material. When the ID / IG ratio of the graphite material is within the above range, the graphite material has good crystallinity and moderate crystal defects, which helps to promote the rapid deintercalation of lithium ions while maintaining structural integrity, thereby improving the fast charging performance of the battery.

[0091] In some embodiments, the negative electrode material layer includes a first negative electrode film layer and a second negative electrode film layer, the first negative electrode film layer is closer to the negative electrode current collector than the second negative electrode film layer; the particle size Dv50 of the graphite in the first negative electrode film layer is smaller than the particle size Dv50 of the graphite in the second negative electrode film layer. In some embodiments, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer can be 3 to 7:3 to 7, for example, about 1:1, 3:4, 3:5, 1:2, 3:7, 4:3, 4:5, 2:3, 4:7, 5:3, 5:4, 5:6, 5:7, 2:1, 3:2, 6:5, 6:7, 7:3, 7:4, 7:5, 7:6, etc.

[0092] The first negative electrode film layer is farther away from the electrolyte than the second negative electrode film layer, and the resistance of lithium ions embedding into the graphite of the first negative electrode film layer is greater. Therefore, further reducing the particle size of the graphite in the first negative electrode film layer can shorten the lithium ion embedding path and reduce the resistance of lithium ion embedding. Using graphite with a relatively large particle size in the second negative electrode film layer can still meet the demand for lithium ion embedding under fast charging conditions, and also has good dispersibility and processing performance.

[0093] In some embodiments, the particle size Dv50 of the graphite in the first negative electrode film layer is 2 to 15 μm, for example, about 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.; and / or,

[0094] The particle size Dv50 of the graphite in the second negative electrode film layer is 5 to 20 μm, for example, it can be about 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.

[0095] When the graphite particle size in the first negative electrode film layer and / or the second negative electrode film layer is within the above range, it is beneficial to further improve the lithium ion embedding ability during the fast charging process.

[0096] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0097] In some embodiments, the negative electrode plate further includes a primer layer disposed between the negative current collector and the negative electrode material layer. The primer layer may be a primer layer for batteries known in the art, and is generally formed by a primer slurry including a conductive agent, a binder, a dispersant, and deionized water. The conductive agent, the binder, and the dispersant may be a conductive agent, a binder, and a dispersant for batteries known in the art. By further including a primer layer, the bonding force between the active material and the current collector may be increased, so that the pole piece is not prone to powdering or film removal during the charge and discharge process.

[0098] In some embodiments, the negative electrode material layer includes a binder, and the binder can be a material known in the art, for example, the binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0099] In some embodiments, the negative electrode active material does not contain any other materials except the graphite. In some embodiments, the negative electrode active material may further include at least one of the following materials: soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0100] In some embodiments, the negative electrode material layer does not contain other conductive agents except the linear conductive agent. In some embodiments, the negative electrode material layer optionally further includes other conductive agents; for example, it can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, and carbon dots.

[0101] In some embodiments, the negative electrode material layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0102] In some embodiments, a method for preparing the negative electrode sheet is provided, wherein the graphite, the linear conductive agent and any other components (such as a binder, etc.) are dispersed in a solvent (such as deionized water) to prepare a negative electrode slurry; the negative electrode slurry is coated on a negative electrode collector, and after drying, drying, cold pressing and other processes, a negative electrode sheet can be obtained.

[0103] In some embodiments, graphite with element doping can be prepared according to the following method, using chemical vapor deposition (CVD), introducing a doping element precursor at high temperature to perform element doping. For example, ammonia water is introduced to achieve N element doping, sodium hypophosphite is introduced to achieve P element doping, and thiophene is introduced to achieve S element doping. In some embodiments, P element doping is performed according to the following method: a certain amount of sodium hypophosphite is placed upstream of the road, argon gas is introduced at 100 ml / min, and the temperature is raised to 800°C after 30 minutes, and maintained for 2-20 hours. In this process, the atomic ratio of the doping element to the carbon element can be adjusted mainly by adjusting the time of introducing the precursor or the time of chemical vapor deposition.

[0104] In some embodiments, the graphite surface also has an amorphous carbon coating layer, which can be carried out after or simultaneously with the step of element doping, by introducing a carbon-containing gas such as methane, ethane, ethylene, acetylene, etc. into the gas path upstream, and coating the amorphous carbon by chemical vapor deposition. In this process, the thickness of the amorphous carbon coating layer can be adjusted mainly by adjusting the time of introducing the carbon-containing gas or the time of chemical vapor deposition.

[0105] [Positive electrode]

[0106] The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material.

[0107] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0108] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0109] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, sodium transition metal oxides, polyanionic compounds, Prussian blue compounds and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0110] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0 <x≤1。

[0111] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.

[0112] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.

[0113] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.

[0114] Polyanionic compounds include NaFePO4, Na3V2(PO4)3, NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0115] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 <a≤2,0<b<1,0<c<1。

[0116] In some embodiments, the positive electrode material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0117] In some embodiments, the positive electrode material layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0118] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0119] [Electrolytes]

[0120] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0121] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0122] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0123] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0124] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0125] [Isolator]

[0126] In some embodiments, the electrode assembly further includes a separator disposed between the positive electrode sheet and the negative electrode sheet.

[0127] In some embodiments, the separator is a separator. The present application has no particular limitation on the type of separator, and any known separator with a porous structure having good chemical stability and mechanical stability can be selected.

[0128] As an example, the main material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without special restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions. The separator can be a separate component located between the positive and negative electrodes, or it can be attached to the surface of the positive and negative electrodes. An inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating can also be coated on the surface of the separator.

[0129] In some embodiments, the separator is a solid electrolyte, which is disposed between the positive electrode and the negative electrode and serves to transmit ions and isolate the positive and negative electrodes.

[0130] [Structure of electrode assembly]

[0131] The electrode assembly may be a wound structure, a laminated structure, or a mixed structure of a wound structure and a laminated structure.

[0132] In some embodiments, the electrode assembly is a wound structure, wherein the positive electrode sheet and the negative electrode sheet are wound into the wound structure.

[0133] In some embodiments, the electrode assembly is a laminate structure.

[0134] As an example, a plurality of positive electrode sheets and a plurality of negative electrode sheets may be provided respectively, and the plurality of positive electrode sheets and the plurality of negative electrode sheets may be alternately stacked.

[0135] As an example, a plurality of positive electrode sheets may be provided, and the negative electrode sheet is folded to form a plurality of stacked folded segments, with a positive electrode sheet sandwiched between adjacent folded segments.

[0136] As an example, both the positive electrode sheet and the negative electrode sheet are folded to form a plurality of stacked folded sections.

[0137] As an example, a plurality of separators may be provided, each of which is provided between any adjacent positive electrode sheets or negative electrode sheets.

[0138] As an example, the separator may be disposed continuously, and may be disposed between any adjacent positive electrode sheets or negative electrode sheets by folding or winding.

[0139] In some embodiments, the shape of the electrode assembly can be cylindrical, flat, or polygonal.

[0140] In some embodiments, the electrode assembly is provided with tabs, which can lead current out of the electrode assembly. The tabs include a positive tab and a negative tab.

[0141] [shell]

[0142] In some embodiments, the battery cell may include a shell. The shell may be a steel shell, an aluminum shell, a plastic shell (such as polypropylene), a composite metal shell (such as a copper-aluminum composite shell) or an aluminum-plastic film, etc. In some embodiments, the shell may be a sealed structure or a non-sealed structure. As an example, when the shell is a non-sealed structure, the shell plays a role in protecting the electrode assembly, and a sealed bag is also included between the shell and the electrode assembly, and the sealed bag is used to encapsulate the electrode assembly and the electrolyte. Specifically, the sealed bag may be a bag-shaped insulating member or an aluminum-plastic film. When the shell is a sealed structure, it is used to encapsulate components such as the electrode assembly and the electrolyte.

[0143] As an example, the battery cell may be a cylindrical battery cell, a prismatic battery cell, a soft-pack battery cell or a battery cell of other shapes, and the prismatic battery cell includes a square-shell battery cell, a blade-shaped battery cell, a multi-prismatic battery, and the multi-prismatic battery is, for example, a hexagonal battery, etc., and the present application has no particular limitation. For example, Figure 1 The battery cell 5 is a square case as an example.

[0144] In some embodiments, reference Figure 2 The housing includes an end cap 53 and a shell 51, the shell 51 is provided with an opening, and the end cap 53 is provided to cover the opening. The shell 51 may be provided with one or more openings. One or more end caps 53 may also be provided. The positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is encapsulated in a receiving cavity enclosed by the shell 51 and the end cap 53. The electrolyte is impregnated in the electrode assembly 52.

[0145] [Electrode terminal]

[0146] In some embodiments, at least one electrode terminal is disposed on the housing, and the electrode terminal is electrically connected to the electrode tab. The electrode terminal may be directly connected to the electrode tab, or may be indirectly connected to the electrode tab through a current collecting member. The electrode terminal may be disposed on an end cap, or may be disposed on the housing.

[0147] [Pressure relief mechanism]

[0148] In some embodiments, a pressure relief mechanism is provided on the housing, and the pressure relief mechanism is used to discharge the internal gas of the battery cell.

[0149] As an example, when the internal pressure or temperature of the battery cell reaches a predetermined threshold, it is actuated to release the internal pressure or temperature. When the internal pressure or temperature of the battery cell reaches a predetermined threshold, the pressure relief mechanism performs an action or a weak structure provided in the pressure relief mechanism is destroyed, thereby forming an opening or channel for the internal pressure or temperature to be released. The threshold design varies according to different design requirements. The threshold may depend on one or more materials of the positive electrode plate, negative electrode plate, electrolyte and separator in the battery cell.

[0150] As an example, the pressure relief mechanism may be integrally formed with the housing.

[0151] As an example, the pressure relief mechanism may also be separately provided and connected to the housing.

[0152] The "actuation" mentioned in this application means that the pressure relief mechanism is in action or activated to a certain state, so that the internal pressure and temperature of the battery cell can be released. The action produced by the pressure relief mechanism may include but is not limited to: the components in the pressure relief mechanism move to form an exhaust channel, at least a part of the pressure relief mechanism ruptures, breaks, is torn or opened, etc. When the pressure relief mechanism is actuated, the high-temperature and high-pressure substances inside the battery cell will be discharged from the actuated part as emissions. In this way, the battery cell can be depressurized and cooled under controllable pressure or temperature, thereby avoiding potential more serious accidents.

[0153] In some embodiments, when the outer shell is a non-sealed structure, the pressure relief mechanism can be set as a through hole to discharge the gas inside the battery cell.

[0154] The emissions from the battery cells mentioned in this application include, but are not limited to: electrolyte, dissolved or split positive and negative electrode sheets, fragments of separators, high-temperature and high-pressure gases produced by the reaction, flames, and the like.

[0155] Battery device

[0156] The battery apparatus mentioned in the embodiments of the present application may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells, which are connected in series, in parallel or in mixed connection through a busbar component.

[0157] In some embodiments, a battery cell assembly is generally formed by arranging a plurality of battery cells.

[0158] As an example, the battery cell assembly may be a battery module, which is formed by arranging and fixing a plurality of battery cells to form an independent module. As an example, the battery module may be formed by bundling a plurality of battery cells by a cable tie. Figure 3 This is a battery module 4 as an example. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner.

[0159] In some embodiments, the battery device may be a battery pack, which includes a case and one or more battery cell assemblies, wherein the battery cell assemblies are accommodated in the case.

[0160] As an example, the battery cell assembly may be a battery module, and the battery cell assembly may be accommodated in the box by fixing the battery module in the box. Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a box and a plurality of battery modules 4 disposed in the box. The box includes an upper box 2 and a lower box 3. The upper box 2 can cover the lower box 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0161] As an example, the battery cell assembly may also be housed in the case by directly fixing a plurality of battery cells to the case.

[0162] As an example, the box may include a first box and a second box. The first box and the second box are buckled together to form a closed space inside the box to accommodate the battery cell assembly. The closed here means covered or closed, which can be sealed or unsealed. The first box can be a top cover or a bottom plate.

[0163] As an example, the box body may include a top cover, a frame and a bottom plate. The top cover and the bottom plate are respectively connected to the frame, so that a closed space is formed inside the box body to accommodate the battery cell assembly.

[0164] In some embodiments, the box body can be used as a part of the chassis structure of the vehicle. For example, part of the box body can become at least a part of the floor of the vehicle, or part of the box body can become at least a part of the cross beam and longitudinal beam of the vehicle.

[0165] Electrical devices

[0166] The technical solutions described in the embodiments of the present application are applicable to various electrical devices that use battery cells, such as mobile phones, portable devices, laptop computers, electric vehicles, electric toys, electric tools, vehicles, ships and spacecraft, for example, spacecraft include airplanes, rockets, space shuttles and spacecraft, etc. Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0167] Example 1

[0168] This embodiment provides a lithium ion battery, and the preparation method thereof includes:

[0169] (I) Negative electrode

[0170] 1. Modified graphite

[0171] Put graphite in a porcelain boat container, put it in the middle of a tube furnace and seal it. Introduce argon gas in front of the tube furnace at a flow rate of 100 ml / min. After 30 minutes, start heating at 5°C / min until the temperature reaches 800°C, then keep it warm for 12 hours. During the heat preservation period, introduce ammonia water as a doping precursor, and then naturally cool it to room temperature. Modified graphite is prepared, which is doped with N element, and the atomic ratio of N element to carbon element is 1%; the particle size Dv50 of the modified graphite is 8.8μm, and the Raman spectrum is detected at 1300-1400cm -1 The peak intensity ID in the range of 1550-1650cm -1 The intensity ratio ID / IG of the peak intensity IG within the range is 0.9.

[0172] 2. Preparation of negative electrode sheet

[0173] The modified graphite, single-walled carbon nanotubes (tube diameter 10 nm, length 30 μm, aspect ratio 3000) as linear conductive agents, carboxymethyl cellulose (CMC) as thickener, and styrene-butadiene rubber (SBR) as binder are mixed in a mass ratio of 96.1:0.5:1.4:2 to obtain a negative electrode mixed powder. The negative electrode mixed powder and deionized water are evenly stirred with a vacuum mixer to form a negative electrode slurry. The negative electrode slurry is evenly coated on a copper foil as a negative electrode collector to form a negative electrode material layer. The negative electrode collector coated with the negative electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain a negative electrode sheet, wherein the thickness of the negative electrode material layer on one side of the negative electrode collector is 60 μm.

[0174] (ii) Positive electrode

[0175] Lithium iron phosphate as a positive electrode active material, carbon black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder are mixed in a mass ratio of 96:2:2 to obtain a positive electrode mixed powder, and the positive electrode mixed powder and N-methylpyrrolidone (NMP) are evenly stirred using a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil as a positive electrode current collector, and the positive electrode current collector coated with the positive electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain a positive electrode sheet.

[0176] (III) Isolation film

[0177] A polyethylene (PE) separator with a ceramic particle coating is used.

[0178] (IV) Electrolyte

[0179] Ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a weight ratio of 3:1:1:1 to obtain an organic solvent, and then lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0180] (V) Lithium-ion battery

[0181] The positive electrode sheet, negative electrode sheet and isolation film prepared above are stacked in order so that the isolation film is between the positive and negative electrode sheets, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, injected with electrolyte after drying, and subjected to vacuum packaging, standing, formation, secondary injection, aging and other processes to obtain a lithium-ion battery.

[0182] The following tests were performed and the results are shown in Table 1.

[0183] 1. Rate charging test:

[0184] At room temperature, the prepared lithium-ion battery was fully discharged at a current of 0.33C (discharge cut-off voltage was 2.0V), and charged at a gradient rate of 2-10C (the charging rate gradient was 0.5C, i.e., 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10C, respectively) to a fully charged state (charging cut-off voltage was 3.8V), and the charge and discharge cycle was repeated 10 times. After completion of full charging, the battery cell was disassembled, the lithium plating of the negative electrode sheet was observed, and the maximum rate without lithium plating was recorded.

[0185] 2. Expansion rate of negative electrode when fully charged

[0186] The thickness of the negative electrode sheet prepared by rolling and slitting was measured and recorded as h0. At room temperature, the lithium-ion battery was fully charged at a rate of 0.33C (the charging cut-off voltage was 3.8V), and then the negative electrode sheet was disassembled and a section was taken to measure the thickness with a micrometer, recorded as h1. The expansion rate of the fully charged negative electrode sheet = (h1-h0) / h0×100%.

[0187] Comparative Example 1

[0188] The single-walled carbon nanotubes were prepared and tested in the same manner as in Example 1, except that the diameter of the single-walled carbon nanotubes was 20 nm, the length was 0.7 μm, and the aspect ratio was 35. The results are shown in Table 1.

[0189] Comparative Example 2

[0190] The single-walled carbon nanotubes were prepared and tested in the same manner as in Example 1, except that the diameter of the single-walled carbon nanotubes was 5 nm, the length was 60 μm, and the aspect ratio was 12000. The results are shown in Table 1.

[0191] Comparative Example 3

[0192] Except that unmodified graphite material was used as the negative electrode active material, the preparation and testing were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0193] Comparative Example 4

[0194] Except that the particle size Dv50 of the modified graphite is 1.5 μm, the preparation and detection are carried out in the same manner as in Example 1. The results are shown in Table 1.

[0195] Comparative Example 5

[0196] Except that the particle size Dv50 of the modified graphite is 25 μm, the preparation and detection are carried out in the same manner as in Example 1. The results are shown in Table 1.

[0197] Table 1

[0198] Maximum magnification Negative electrode expansion rate Example 1 6.5 19.3% Comparative Example 1 3.5 27.4% Comparative Example 2 2.5 26.4% Comparative Example 3 4 25.5% Comparative Example 4 2.5 28.6% Comparative Example 5 3.5 24.9%

[0199] By comparing Example 1 and Comparative Example 3, it can be seen that by modifying graphite with element doping, the negative electrode expansion problem is significantly improved, and the maximum rate of the battery is increased. By comparing Example 1 and Comparative Examples 1-2, 4-5, it can be seen that the particle size of the graphite material and the aspect ratio of the linear conductive agent will have a significant impact on the fast charging performance of the battery. If the above two parameters are too high or too low, the fast charging performance of the battery will be deteriorated.

[0200] Embodiments 2 to 9

[0201] Except that the particle size Dv50 of the modified graphite in the negative electrode sheet and the tube diameter and length of the linear conductive agent are shown in Table 2, the preparation and testing are carried out in the same manner as in Example 1. The results are shown in Table 2.

[0202] Table 2

[0203]

[0204] Referring to Table 2, by comparing Examples 1 to 3, it can be seen that when the graphite particle size Dv50 is greater than 5 μm and less than or equal to 10 μm, selecting an appropriate linear conductive agent aspect ratio (Examples 1 to 2, whose aspect ratios meet 2000 to 5000) can be more conducive to improving the fast charging performance of the battery relative to other aspect ratios (Example 3, whose aspect ratio is smaller). By comparing Examples 4 to 6, it can be seen that when the graphite particle size Dv50 is greater than or equal to 2 μm and less than or equal to 5 μm, selecting an appropriate linear conductive agent aspect ratio (Examples 4 to 5, whose aspect ratios meet 5000 to 10000) can be more conducive to improving the fast charging performance of the battery relative to other aspect ratios (Example 6, whose aspect ratio is smaller). By comparing Examples 7 to 9, it can be seen that when the graphite particle size Dv50 is greater than 10 μm and less than or equal to 20 μm, selecting an appropriate aspect ratio of the linear conductive agent (Examples 7 to 8, whose aspect ratios are in the range of 5000 to 10000) can be more conducive to improving the fast charging performance of the battery relative to other aspect ratios (Example 9, whose aspect ratio is smaller).

[0205] Embodiments 10 to 13

[0206] Except that the mass proportion of the linear conductive agent in the negative electrode mixed powder and the specific materials of the linear conductive agent are shown in Table 3 (when the mass proportion of the linear conductive agent changes, the mass proportion of the negative electrode active material changes accordingly, and the mass proportion of the thickener and the binder remains unchanged), preparation and testing were carried out in the same manner as in Example 1, and the results are shown in Table 3.

[0207] Table 3

[0208]

[0209] Embodiments 14 to 17

[0210] The same preparation and testing methods as in Example 1 were used, except that the doping element precursor and its introduction time were changed so that the element doping types and the atomic ratio of the doping element to carbon in the modified graphite were as shown in Table 4. The results are shown in Table 4.

[0211] Table 4

[0212]

[0213]

[0214] Embodiment 18

[0215] Except that the preparation method of modified graphite is as follows, the preparation and detection are carried out in the same manner as in Example 1. The results are shown in Table 5.

[0216] Modified graphite preparation method:

[0217] Graphite is placed in a porcelain boat container, placed in the middle of a tubular furnace and sealed, and argon gas is introduced in front of the tubular furnace with a gas flow of 100 ml / min. After 30 minutes, the temperature begins to rise at 5°C / min until the temperature reaches 800°C, and then it is kept warm for 12 hours. During the insulation period, ammonia water as a doping precursor and methane as a coating layer precursor are introduced, and then the temperature is naturally cooled to room temperature to prepare modified graphite, which, in addition to the characteristics of the modified graphite in Example 1, also has an amorphous carbon coating layer with a thickness of 2 nm.

[0218] Examples 19 to 21

[0219] The same preparation and testing methods as in Example 18 were followed, except that the thickness of the amorphous carbon coating layer of the modified graphite was adjusted mainly by adjusting the time for introducing the coating layer precursor as shown in Table 5. The results are shown in Table 5.

[0220] Table 5

[0221]

[0222] Referring to Table 5, when amorphous carbon coating is applied, it is beneficial to further improve the negative electrode expansion problem of the battery, and when the amorphous carbon coating has a certain thickness (thickness is 10 to 20 nm, see Examples 20 and 21), it can also improve the fast charging performance.

[0223] Embodiments 22 to 24

[0224] The same preparation and testing methods as in Example 1 were followed, except that the ID / IG of the modified graphite was adjusted as shown in Table 6 by selecting graphite with corresponding ID / IG values. The results are shown in Table 6.

[0225] Table 6

[0226] ID / IG Maximum magnification Negative electrode expansion rate Example 1 0.9 6.5 19.3% Embodiment 22 0.5 5.5 20.4% Embodiment 23 1.2 6 22.5% Embodiment 24 1.5 4.5 24.3%

[0227] Examples 25 to 27

[0228] Except for preparing the negative electrode sheet by the following method, the preparation and testing were carried out in the same manner as in Example 1. The results are shown in Table 7.

[0229] 1. Preparation of modified graphite

[0230] According to the preparation method of modified graphite in Example 1, by changing the particle size of unmodified graphite, modified graphites with particle sizes Dv50 of 3, 10, and 15 μm were obtained respectively.

[0231] 2. Preparation of negative electrode sheet

[0232] First negative electrode slurry: The first negative electrode mixed powder was prepared according to the method for preparing the negative electrode mixed powder in Example 1, wherein the particle size Dv50 of the modified graphite and the aspect ratio of the linear conductive agent were as shown in Table 7. The first negative electrode mixed powder and deionized water were stirred evenly with a vacuum mixer to form a first negative electrode slurry.

[0233] Second negative electrode slurry: According to the method for preparing the negative electrode mixed powder in Example 1, a second negative electrode mixed powder was prepared, wherein the particle size Dv50 of the modified graphite and the aspect ratio of the linear conductive agent were as shown in Table 7. The second negative electrode mixed powder and deionized water were stirred evenly with a vacuum mixer to form a second negative electrode slurry.

[0234] Negative electrode sheet: firstly, the first negative electrode slurry is evenly coated on the copper foil as the negative electrode current collector to form the first negative electrode film layer, and then the second negative electrode slurry is evenly coated on the surface of the first negative electrode film layer after drying, and then the negative electrode sheet is obtained after drying, rolling and cutting.

[0235] Table 7.

[0236]

[0237]

[0238] Referring to Table 7, the maximum rate of the battery is further significantly improved by the method of layered design of the negative electrode material layer of Examples 25 to 27.

[0239] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A battery cell, characterized in that: It includes a positive electrode sheet, a separator and a negative electrode sheet; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; the negative electrode material layer comprises a negative electrode active material and a conductive agent; The negative electrode active material includes graphite, the particle size Dv50 of the graphite is 2 to 20 μm, the graphite includes a doping element, and the atomic radius of the doping element is greater than the atomic radius of the carbon element; The conductive agent includes a linear conductive agent, and the aspect ratio of the linear conductive agent is 50 to 10,000.

2. The battery cell according to claim 1, characterized in that: The doping element includes one or more of nitrogen, phosphorus and sulfur.

3. The battery cell according to claim 1 or 2, characterized in that: The particle size Dv50 of the graphite and the aspect ratio of the linear conductive agent meet one of the following conditions: The particle size Dv50 of the graphite is greater than or equal to 2 μm and less than or equal to 5 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 5000 and less than or equal to 10000; or, The particle size Dv50 of the graphite is greater than 5 μm and less than or equal to 10 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 2000 and less than 5000; or, The particle size Dv50 of the graphite is greater than 10 μm and less than or equal to 20 μm, and the aspect ratio of the linear conductive agent is greater than or equal to 50 and less than 2000.

4. The battery cell according to any one of claims 1 to 3, characterized in that: In the negative electrode material layer, the mass ratio of the linear conductive agent is 0.02% to 1% based on the mass of the negative electrode material layer.

5. The battery cell according to any one of claims 1 to 4, characterized in that: The diameter of the linear conductive agent is 5 to 20 nm; and / or, The length of the linear conductive agent is 1 to 200 μm.

6. The battery cell according to any one of claims 1 to 5, characterized in that: The linear conductive agent comprises at least one of the following groups: single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanofibers.

7. The battery cell according to any one of claims 1 to 6, characterized in that: In the graphite, the atomic ratio of the doping element to the carbon element is 0.5% to 2%.

8. The battery cell according to any one of claims 1 to 7, characterized in that: At least part of the surface of the graphite has an amorphous carbon coating layer; the thickness of the amorphous carbon coating layer is 2-20 nm.

9. The battery cell according to any one of claims 1 to 8, characterized in that: The graphite is measured by Raman spectroscopy at 1300-1400 cm -1 The peak intensity ID in the range of 1550-1650cm -1 The intensity ratio ID / IG of the peak intensity IG within the range is 0.5 to 1.

5.

10. The battery cell according to any one of claims 1 to 9, characterized in that: The negative electrode material layer includes a first negative electrode film layer and a second negative electrode film layer, the first negative electrode film layer is closer to the negative electrode current collector than the second negative electrode film layer; the particle size Dv50 of the graphite in the first negative electrode film layer is smaller than the particle size Dv50 of the graphite in the second negative electrode film layer.

11. The battery cell according to any one of claims 1 to 10, characterized in that: The particle size Dv50 of the graphite in the first negative electrode film layer is 2 to 15 μm; and / or, The particle size Dv50 of the graphite in the second negative electrode film layer is 5 to 20 μm.

12. A battery device, characterized in that: The battery device includes the battery cell according to any one of claims 1 to 11.

13. An electrical device, characterized in that: The electrical device comprises the battery cell according to any one of claims 1 to 11 or the battery device according to claim 12.